Pengaruh Media Pembelajaran Google Classroom Dalam Pembelajaran SPLDV Terhadap Hasil Belajar Siswa - Daeng Lauq, Surya Gunawan; Sukarma, I Ketut; Yuntawati, Yuntawati (Media Pendidikan Matematika, 2022)
This study aims to determine whether or not the influence of google classroom learning media on student learning outcomes at SMAN 3 Selong and to determine students’ abilities in learning mathematics in SPLDV by using google classroom media on students at SMAN 3 Selong. The type of research used in this research is field research. Field research is research that is carried out by going directly into the field to examine the use of google classroom in understanding concepts in SPLDV learning on student learning outcomes at SMAN 3 Selong. The subjects of this study were 44 students from the entire research population, which were taken from students who used the Google Classroom learning media, 22 students and 22 students who did not use the Google Classroom learning media. Based on the research and data analysis that has been done, it can be concluded that there is an effect of using google classroom media on student learning outcomes in learning mathematics on SPLDV material for SMAN 3 Selong students. This is because the Google Classroom media is easy to use, cloud-based, flexible, and easy to use on any mobile device. Google Classroom is also not only a place for collecting assignments, but also can take advantage of several features to create virtual classes in Google Classroom by providing implementation procedures.